One step eco-friendly synthesis of Ag–reduced graphene oxide nanocomposite by phytoreduction for sensitive nitrite determination. Issue 102 (21st October 2016) - Shaikh, Aasiya; Parida, Smrutiranjan; Böhm, Sivasambu
Abstract : One step green synthesis of a silver–reduced graphene oxide nanocomposite (Ag–RGO) and its application to construct a nitrite (NO2 − ) sensor. Abstract : We report a facile, ecofriendly, surfactant-free one step green synthesis of a silver–reduced graphene oxide nanocomposite (Ag–RGO) using a Justicia adhatoda (adulsa) leaf extract as green reducing agent and its application to construct a nitrite (NO2 − ) sensor. The crystallinity, size, morphology and composition of as prepared Ag–RGO nanocomposite were studied using a range of techniques. TEM results showed that ultrasmall silver nanoparticles (2–4 nm) were well dispersed on RGO sheets with C/O ratio of 4.4 and 63.8% of sp 2 carbon, obtained from XPS analysis. These results confirmed that adulsa leaf extract not only simultaneously reduce silver ion and graphene oxide but also act as effective capping agent. Electrochemical investigations indicated that Ag–RGO nanocomposite had excellent catalytic activity towards nitrite oxidation with sensitive nitrite detection below 1 ppm. The sensor exhibited two linear ranges; one from 10 nM to 1000 nM with a sensitivity of 3.0 × 10 4 μA mM −1 cm −2 ( R = 0.999) and another from 10 μM to 1000 μM with a sensitivity of 373.46 μA mM −1 cm −2 ( R = 0.978). These values are superior to other previously reported NO2 − sensors.